2011
DOI: 10.1002/meet.2011.14504801242
|View full text |Cite
|
Sign up to set email alerts
|

Social media discomfort: The clash between the old and the new at work

Abstract: This research investigates a conventional professional work practice and hesitant attitudes and feelings related to an introduction of a social media tool for communication and collaboration. The study was conducted at a wellestablished, international product development company in the electronic industry. Semi-structured in-depth interviews were carried out with engineers from the company's R&D site. Based on the data analysis, the key findings focus upon a perception of Social Media Discomfort (SMD). Factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The dropbox can be regarded as one of several contemporary web‐based technologies that are often categorized as participatory or social media and are therefore charged with a certain energy that sometimes evokes rather strong opinions and emotions: what Forsgren and Byström () term “social media discomfort.” It may give rise to the use of dichotomies such as new and old, modern and old‐fashioned. It is thus not only the function but also the perceived “newness” that is potentially attractive or unattractive.…”
Section: Resultsmentioning
confidence: 99%
“…The dropbox can be regarded as one of several contemporary web‐based technologies that are often categorized as participatory or social media and are therefore charged with a certain energy that sometimes evokes rather strong opinions and emotions: what Forsgren and Byström () term “social media discomfort.” It may give rise to the use of dichotomies such as new and old, modern and old‐fashioned. It is thus not only the function but also the perceived “newness” that is potentially attractive or unattractive.…”
Section: Resultsmentioning
confidence: 99%
“…Although positive experiences with ESMPs in particular organizations, researchers also point out the challenges with adopting and implementing the same technology in organizations. Researchers use different terminologies to describe this phenomena, like "social networking effectiveness" (Figueiredo et al 2009), "social media discomfort" (Forsgren and Byström 2011) or "IT-culture conflict" (Koch et al 2013). Therefore, this research stream is called "ESMP skepticism and challenges" and counts 7 journal and research papers.…”
Section: Research Stream 2: Esmp Skepticism and Challengesmentioning
confidence: 99%
“…Similarly, in terms of information sharing, DiMicco et al () identified three strategies—caring, climbing, and campaigning—used by the employees in a social networking site. Finally, discomfort to expose one's expertise in social media is another factor that can influence adoption and differs amongst employees (Forsgren & Byström, ).…”
Section: Introductionmentioning
confidence: 99%